Aktivitas dan Prestasi Belajar melalui Penerapan Metode Permainan di Kelas V SD N 09 Batang Anai Kabupaten Padang Pariaman - Dalimasni Dalimasni (Naradidik: Journal of Education and Pedagogy, 2022)
The objectives of this Classroom Action Research (CAR) are to improve students' mathematics learning activities, and 2) to improve the mathematics learning achievement of students. The research was carried out in two (2) cycles each consisting of two (2) meetings through the following stages of planning, observation, and reflection. The results obtained from CAR through the game method model showed an increase in the results of student activities, especially in activities to prepare places, materials, and tools by 54,71 %, activities to express ideas by 65,12 %, and for activities to read game rules and books experienced by 73,02 %. Based on the student's mathematics learning achievement data, the average grade in cycle 1 was 65,12, increasing to 71,91 in cycle 2. The percentage of students who achieved the standard of completeness also increased in cycle 2 by 87,18 % (good category), increasing to 100 % (special category) in cycle 2.